2008
DOI: 10.1080/02841850701793777
|View full text |Cite
|
Sign up to set email alerts
|

Role of scintigraphy with technetium-99m depreotide in the diagnosis and management of patients with suspected lung cancer

Abstract: 99mTc-depreotide scintigraphy has a high sensitivity in detecting lung cancer. The method is useful in decision-making with respect to surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Still, this is somewhat lower than both the sensitivity for detecting lung cancers [2, 611] with the same tracer and that for detecting lung cancer with 18 F-FDG-PET [68]. While 18 F-FDG uptake reflects a metabolic activity of the lesion and is not specific to tumors [68], overexpression of somatostatin receptors on tumor cells could give another valuable piece of information regarding tumor properties.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Still, this is somewhat lower than both the sensitivity for detecting lung cancers [2, 611] with the same tracer and that for detecting lung cancer with 18 F-FDG-PET [68]. While 18 F-FDG uptake reflects a metabolic activity of the lesion and is not specific to tumors [68], overexpression of somatostatin receptors on tumor cells could give another valuable piece of information regarding tumor properties.…”
Section: Discussionmentioning
confidence: 99%
“…We used the same starting point for the imaging session as for the standard procedure in the detection of lung cancer, that is, 2 hours after injection [8, 10, 11]. During the last decade there has been a trend of performing a double-phase registration in order to increase specificity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 99m Tc-labeled agent, 99m Tc-Depreotide, has received regulatory approval in the United States and Europe for use in the detection of lung cancer [ 50 ]. It binds to a wide range of SSTR subtypes (SSTR2, SSTR3, and SSTR5) and has shown promise in diagnosing a variety of tumor types [ 51 – 53 ], including some OctreoScan negative NETs [ 10 ]. 111 In-DOTA-lanreotide is another γ -emitting tracer with different affinity for SSTR subtypes compared to [ 111 In-DTPA 0 ]octreotide.…”
Section: Somatostatin Receptor Based Imagingmentioning
confidence: 99%
“…99m Tc-depreotide scintigraphy has been shown to be a potentially valuable tool in the diagnosis of solitary pulmonary nodules and lymph node metastases [2, 710]. Our initial experience has also revealed that scintigraphic examination with 99m Tc-depreotide is feasible for imaging of oesophageal cancer [11].…”
Section: Introductionmentioning
confidence: 99%